Mathematical model of steel lazy-wave riser abandonment and recovery in deepwater. (April 2015) - Wang, Jinlong; Duan, Menglan; Luo, Jianmei
Abstract: To meet the increasing applications of the deepwater steel lazy-wave riser (SLWR), the riser abandonment and recovery (A&R) is a great challenge for SLWR installation and its mechanical analysis is necessary and significant. This paper is focused on the abandonment and recovery process which is of great importance to the installation feasibility and analysis. A comprehensive mechanical model based on the nonlinear large deformation beam theory for simulating the deepwater SLWR is proposed. And a simple and suitable model for analyzing the A&R cable is developed. The presented model with detailed boundary conditions is able to deal with three different A&R methods. Numerical analysis is conducted by the finite difference method to investigate the riser configurations and somev important mechanical parameters of the pipeline and cable which exert influences on the riser's performance and the A&R cable's requirement. Parametric comparison study is conducted to analyze the advantage of different method. The proposed model can help on development of deepwater SLWR A&R design and analysis. Highlights: A mathematical model for deepwater SLWR abandonment and recovery is proposed. The A&R system comprising pipelines, A&R cable and installation vessel is considered. Numerical analysis for three different A&R methods is conducted. The proposed model can help on development of deepwater SLWR A&R design and analysis.